Thermal modeling for a parent body of Itokawa. (2nd August 2013) - Wakita, S.; Nakamura, T.; Ikeda, T.; Yurimoto, H.
Abstract We modeled the possible parent bodies of Itokawa, which was heated within by the decay energy of 26Al. Based on mineralogic studies of dust particles derived from Itokawa by the Hayabusa spacecraft, it appeared that they were thermally metamorphosed at a peak temperature of 800 °C, and kept at 700 °C or higher at 7.6 Myr after CAI formation. Our numerical results show that the parent bodies of Itokawa would have been larger than 20 km in radius and accreted at a period between 1.9 and 2.2 Myr after CAI formation, to satisfy mineralogic and isotopic evidence from dust particles.